Optical and electrochemical behaviour of the adsorption of potassium ethyl xanthate on gold - Lezna, Reynaldo Oscar (1988)
The first stages of the electroadsorption of ethyl xanthate (EX) on polycrystalline gold have been studied by optical and electrochemical techniques covering the 5 × 10−6 to 1 × 10−3 M concentration range. According to ac voltammetry and electroreflectance measurements, the adsorption of EX begins at −1.4 V (vs. SCE), in the HER potential region, followed by a capacitative process at −1.0 V. Both stages can be ascribed to the formation of different bonds between the EX and the gold surface through the sulphur atoms of the molecule. The following electroadsorption stage at −0.7 V implies the formation of a surface compound leading subsequently to layer growth. Differential reflectivity was particularly useful in providing information'on this type of complex adsorption process without appreciable interference from charging currents or stray faradaic reactions.